2020
DOI: 10.3390/molecules25071746
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents with GNMT-Promoter-Enhancing and NRF2-Reduction Activities from Taiwan Agarwood Excoecaria formosana

Abstract: Hepatocellular carcinoma (HCC) is considered to be a silent killer, and was the fourth leading global cause of cancer deaths in 2018. For now, sorafenib is the only approved drug for advanced HCC treatment. The introduction of additional chemopreventive agents and/or adjuvant therapies may be helpful for the treatment of HCC. After screening 3000 methanolic extracts from the Formosan plant extract bank, Excoecaria formosana showed glycine N-methyltransferase (GNMT)-promoter-enhancing and nuclear factor erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 65 publications
1
28
0
Order By: Relevance
“…The UV, IR and 1D NMR spectroscopic data of 5 were very close to those of durantin C ( 6 ) [ 22 ], which was purified from same subfraction by HPLC. Fortunately, there existed a pattern that C-7 (δ C 137.4 in 6 vs. 136.8 in 5 ) was shifted to high field and C-8 (δ C 132.1 in 6 vs. 132.7 in 5 ) shifted to low field when the connection mode converted from C-7–O–C-7′ to C-7–O–C-8′ [ 23 , 24 ]. In view of these similarities, 5 was logically assumed to be the regioisomer of 6 , which was further verified by the HMBC couplings between C-8 and H-7′ (δ H 4.91), and between C-7 and H-9′ (δ H 4.07) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The UV, IR and 1D NMR spectroscopic data of 5 were very close to those of durantin C ( 6 ) [ 22 ], which was purified from same subfraction by HPLC. Fortunately, there existed a pattern that C-7 (δ C 137.4 in 6 vs. 136.8 in 5 ) was shifted to high field and C-8 (δ C 132.1 in 6 vs. 132.7 in 5 ) shifted to low field when the connection mode converted from C-7–O–C-7′ to C-7–O–C-8′ [ 23 , 24 ]. In view of these similarities, 5 was logically assumed to be the regioisomer of 6 , which was further verified by the HMBC couplings between C-8 and H-7′ (δ H 4.91), and between C-7 and H-9′ (δ H 4.07) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…70 Interestingly, a recent drug screening study showed that NRF2 activity is potentially regulated by the oncosuppressor GNMT. 71 Taken together, these observations show that NRF2 is a main regulator of the antioxidative and detoxification responses and propels the progression of cancer, formation of metastases, and resistance to therapy. 72 In addition to mutations in cancer-related genes, HCC tumors harbor mutations in serum proteins such as albumin (ALB) and apolipoprotein B (APOB), which are not frequently mutated in other cancer types.…”
Section: Mutational Landscape Of Hccmentioning
confidence: 86%
“… 70 Interestingly, a recent drug screening study showed that NRF2 activity is potentially regulated by the oncosuppressor GNMT. 71 Taken together, these observations show that NRF2 is a main regulator of the antioxidative and detoxification responses and propels the progression of cancer, formation of metastases, and resistance to therapy. 72 …”
Section: Mutational Landscape Of Hccmentioning
confidence: 86%
“…Luciferase reporter assay and cell viability assay were performed based on methods described in a previous paper [ 22 ]. Relative luciferase activity (RLA) was calculated by normalizing luciferase activity to cell viability.…”
Section: Methodsmentioning
confidence: 99%